The effects of ecolabels on environmentally- and health-friendly cars: an online survey and two experimental studies - Folkvord, Frans; Veltri, Giuseppe A.; Lupiáñez-Villanueva, Francisco; Tornese, Pietro; Codagnone, Cristiano; Gaskell, George (The international journal of life cycle assessment, 2020)
Purpose Given the increasing importance of political decision-making to reduce emission targets, the main purpose of the current paper is to identify and test the considerations that would nudge consumers towards an environmentally and health-friendly motor vehicle. Methods An online survey was conducted to assess public responses and the role of public authorities to a voluntary emission standard for passenger cars. In addition, two online experiments were conducted to test incentives in the design of ecolabels (e.g. price, safety, performance) for optimization. A random sample of 6400 individuals was drawn from eight countries: Germany, Ireland, Italy, the Netherlands, Spain, UK, Czech Republic and Lithuania. An online survey was conducted among 3200 respondents, 400 in each of the 8 countries, and 2 online experiments with 3200 subjects, 400 in each of the 8 countries, allowing for 200 respondents for each experiment in each country. Results and discussion The survey shows that Europeans are aware of the health and environmental impact of cars. The findings also confirm the gap between self-reported attitudes/intentions and actual behaviours. In influencing car purchase decisions, health and environmental concerns are less important than other attributes such as price, safety and performance. The experiments show that all these attributes have a significant effect on consumers’ choices. However, message content was found to have the strongest effect. Respondents are more likely to choose European Union Low Emitting carS (EULES)-friendly cars when the label shows information on lower costs or lower taxes and less likely to be influenced by health-related benefits, convenient parking or access fees. Finally, combinations of one message with other elements—EULES logo, CO 2 logo or both—within the same label have a small but positive effect on respondents’ choices. Conclusions The findings of this study assist governmental decision-making processes by identifying those issues that have the greatest impact on consumers’ car purchasing decisions. Furthermore, the results will help to guide environmentally conscious customers towards the purchase of vehicles with clean emission profiles.